IBM Pelatihan Kader dalam Deteksi Dini Lansia dengan Demensia di Desa Deliksari, Gunungpati, Semarang - Novita Wulan Sari; Margiyati Margiyati; Nanang Khosim A (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to develop a cadre training program in early detection of dementia in the elderly in Deliksari Village, Gunungpati, Semarang. Dementia is an increasingly urgent health problem in Indonesia, including in rural areas such as Deliksari Village. This program uses an educational approach and practical training to increase cadres' knowledge and skills in recognizing early signs of dementia. Training methods include the delivery of theory, case studies, and direct practice in identifying symptoms and behavior that indicate dementia. Program evaluation was carried out to measure the increase in cadres' knowledge and skills in carrying out early detection of dementia. It is hoped that the results of this research can contribute to efforts to prevent and early treat dementia at the rural community level